Women in the Middle of the Wild Life in the East Sumatra Plantation 1880-1940 - Maiza Elvira; Fatima Gay J. Molina; Anne Van der Veer (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Since the enactment of the Koeli Ordonantie in 1880 by the Dutch colonial government, large plantations on the east coast of Sumatra began to open up opportunities for Javanese and Chinese women to be employed as laborers. There are also those who follow their husbands to work on plantations. The planters took advantage of the presence of women on the plantations to create entertainment for the male workers, because at that time many coolies ran away from the plantations, due to the heavy workload. The easy flow of money makes unpaired female workers take advantage of opportunities. They choose dual jobs as laborers during the day, and prostitutes at night. The impact is the spread of various disease outbreaks, one of which is venereal disease. In the context of social history, this research uses archives as its methodology. The archives come from Koloniaal Verslag, Verslagvoor Geneeskundige, Verslag van den Dienst van Arbeidinspectie, Tijdscriftvoor Geneeskundige, reports from Deli Planter Vereneging and Memorie van Overgave, and other support books